When Are Leaders Receptive to Voiced Creative Ideas? Joint Effects of Leaders’ Achievement Goals and Personal Sense of Power - Sijbom, Roy B. L.; Parker, Sharon K. (Frontiers in Psychology, 2020)
Voiced suggestions for improvement and constructive change (i.e., voiced creative ideas) by employees are important for organizations. In order to reap the benefits of these ideas, leaders need to be receptive. Drawing on achievement goal theory and approach-inhibition theory of power, we examined the joint effects of leader achievement goals and personal sense of power on leader receptivity to voiced creative ideas in two studies. In a field study (Study 1, N = 136), we found that leaders pursuing mastery-approach goals were positively related to leader receptivity. Receptivity for leaders pursuing performance-approach goals was found to be contingent upon their personal sense of power, with a positive (negative) association under conditions of high (low) sense of power. Similarly, in experimental study (Study 2, N = 93), in which we manipulated leader achievement goals, the receptivity of performance-approach goal leaders was contingent upon their sense of power. When sense of personal power was high, performance-approach goal leaders displayed higher levels of receptivity than when their personal sense of power was low. An implication is that personal sense of power may prevent leaders with performance-approach goals from disregarding creative ideas that are put forward by their subordinates. These findings extend insight into how and when leaders are receptive to voiced creative ideas.